2016
DOI: 10.1073/pnas.1600359113
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium and nitrite oxidation at nanomolar oxygen concentrations in oxygen minimum zone waters

Abstract: A major percentage of fixed nitrogen (N) loss in the oceans occurs within nitrite-rich oxygen minimum zones (OMZs) via denitrification and anammox. It remains unclear to what extent ammonium and nitrite oxidation co-occur, either supplying or competing for substrates involved in nitrogen loss in the OMZ core. Assessment of the oxygen (O 2 ) sensitivity of these processes down to the O 2 concentrations present in the OMZ core (<10 nmol·L −1 ) is therefore essential for understanding and modeling nitrogen loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
209
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(244 citation statements)
references
References 75 publications
20
209
3
Order By: Relevance
“…Our results show that the photosynthetic community of the SCM produces significant amounts of O 2 , sufficient to maintain an aerobic community in an otherwise anoxic environment. Rates of O 2 production and carbon fixation in the SCM in both ETNP and ETSP AMZs are comparable to previously measured rates of aerobic processes like nitrite and ammonium oxidation (8,17), as well as anaerobic AMZ processes like denitrification, anammox, and sulfate reduction (7,8). Although the measured metabolic rates exhibit large spatial and temporal variability, our data collectively suggest a significant effect of local photosynthesis on the biogeochemical cycling in Pacific Ocean AMZs.…”
supporting
confidence: 87%
“…Our results show that the photosynthetic community of the SCM produces significant amounts of O 2 , sufficient to maintain an aerobic community in an otherwise anoxic environment. Rates of O 2 production and carbon fixation in the SCM in both ETNP and ETSP AMZs are comparable to previously measured rates of aerobic processes like nitrite and ammonium oxidation (8,17), as well as anaerobic AMZ processes like denitrification, anammox, and sulfate reduction (7,8). Although the measured metabolic rates exhibit large spatial and temporal variability, our data collectively suggest a significant effect of local photosynthesis on the biogeochemical cycling in Pacific Ocean AMZs.…”
supporting
confidence: 87%
“…On the other hand, the detection of nitrification during anoxic incubations has been attributed to the persistence of traces of O 2 in the samples (e.g. Bristow et al, 2016;Ganesh et al, 2015), although those studies exhibited caution to O 2 contamination that was similar to this study (see Sect. 2.5 in Methods).…”
Section: Environmental Variabilitysupporting
confidence: 47%
“…However, a dominance of bacterial AO 4808 A. Galán et al: Vertical segregation among pathways mediating nitrogen loss does not correspond to recent molecular and biogeochemical observations from the study area, particularly during the upwelling season, when a high abundance of Thaumarchaeota (previously Crenarchaeota; an archaeon that sustains itself chemolithoautotrophically through aerobic oxidization of NH + 4 ) account for a significant fraction of the microbial assemblage, while ammonium-oxidizing bacteria are scarce or undetectable (Levipan et al, 2007;Quiñones et al, 2009;Bristow et al, 2016). Likewise, the relative contribution to ammonium oxidation, quantified by the ammonia monooxygenase subunit A gene (Molina et al, 2010), and dark carbon assimilation rates (Farías et al, 2009), showed that archaea had a greater potential activity relative to the homologous bacteria in the system.…”
Section: Cycling Of Dissolved Inorganic 15 N Compoundsmentioning
confidence: 69%
“…Element transformations in Oxygen Minimum Zones (OMZs) are very dependent on the local O 2 concentrations, and it has for example been shown that O 2 concentrations below 0.5 µmol L −1 may be strongly inhibitory for denitrification (Dalsgaard et al, 2014;Bristow et al, 2016), but that sub-micromolar O 2 concentrations still allow for high rates of ammonium and nitrite oxidation (Kalvelage et al, 2011(Kalvelage et al, , 2015Füssel et al, 2012;Beman et al, 2013;Bristow et al, 2016). It is thus crucial for our study and understanding of element transformations in OMZ waters that we know exactly which O 2 regime is found in situ, and that we can reproduce this in the laboratory when analyzing rates of element transformations.…”
Section: Introductionmentioning
confidence: 99%